Dying for meat - International Livestock Research Institute (International Livestock Research Institute, 2012)
This photofilm features small-scale butchers and consumers interviewed in Nairobi and a commentary by Delia Grace, an epidemiolgoist at the International Livestock Research Institute (ILRI), on issues that connect animal and human health. This film was made for ILRI by duckrabbit, a UK-based multimedia production company.